Strategies Implemented by Mcdonald’s to Fulfill Customers’ Demand Around Asia - Yusof, Rosmelia; Huei, Lok Yee; Sha’ari, Muhammad Fathi bin; Mazlan, Muhammad Syahmi bin; Othman, Muhammad Amir Muqri bin; Zakaria, Muhammad Badrul Aman bin; Wicaksono, Luqman Juang; Prabawa, Dewa Made Surya; Lakshmi.L, Vinu Surutha; Walde, Kajal Meghshyam (AIBPM Publisher, 2023)
One of the notably popular and well-known fast-food franchises in the known universeis McDonald's. In addition to its renowned golden arches emblem, it is also recognised because of its hamburgers, potato chips, as well as other options. Nevertheless, the goal of this analysis is to investigate the viability of the tactics used by McDonald's to satisfy consumer demands and contentment across Asia. So, in this case study, the research uses an efficient method which is a survey questionnaire to ccumulate useful information of 150 Mcdonald’s customers to know more about their satisfactions towards McDonald’s. The result of the findings shows that perceived usefulness, social influence, perceived innovativeness, and corporate image affect the customer’s satisfaction with McDonald’s. The report's findings will assist the McDonald's corporation in the coming years as they work to enhance their productivity, particularly as it relates to increasing client happiness.